Variability in the Diagnosis and Treatment of Interstitial Cystitis/Bladder Pain Syndrome: Internet Survey - Eleanora Melkonian; A Leigh Garrett; Erika Kline; Pressley Smith; Madelyn Wiesenhahn; Jeanette Petit; Alison Swierczynski; Carley Zhou; Stuart B Bauer; Rosalyn Adam; Kamil E Barbour; Sonja I Ziniel; et al. (JMIR Formative Research)
Abstract BackgroundInterstitial cystitis/bladder pain syndrome (IC/BPS) is a complex, chronic condition affecting the urinary bladder. Symptoms commonly associated with IC/BPS include painful urination, pain during intercourse, a persistent or recurrent sensation of bladder discomfort or pressure that often worsens as the bladder fills and eases after urination, urgency, frequent urination with little warning, nighttime urination disrupting sleep, and burning or other unusual urinary sensations. These symptoms can profoundly impact emotional and mental health, hinder participation in daily activities, disrupt social interactions, and strain personal relationships. ObjectiveThis study aimed to compare the experiences of different races and ethnicities with IC/BPS regarding symptoms, diagnosis, treatment status, and treatment methods. We hypothesized that there would be differences in racial and ethnic minority groups. MethodsA cross-sectional web-based survey was administered between June and August 2022 through the Interstitial Cystitis Association and the Inspire web-based health community. Eligible adults resided in the United States, self-reported IC/BPS symptoms, and completed the survey in English. The instrument gathered demographic information, details regarding age at symptom onset, formal diagnosis status, and treatment use. Validated symptom and problem indices (the O’Leary-Sant Interstitial Cystitis Symptom Index and Problem Index) captured symptom severity and quality-of-life impact. Comparative analyses, including Fisher exact and median tests, were conducted across racial or ethnic groups (minority or multiple-race vs White and Hispanic vs non-Hispanic), and multivariable logistic regression assessed predictors of race or ethnicity on IC/BPS diagnosis status and treatment outcomes. ResultsIn total, 1631 individuals completed the survey. Racial or ethnic minority or multiple-race respondents constituted 11.6% (n=189) of the sample. Although IC/BPS symptom severity (Interstitial Cystitis Symptom Index or Interstitial Cystitis Problem Index scores) did not significantly differ by race or ethnicity, minority or multiple-race respondents were 50% less likely to have a formal medical diagnosis of IC/BPS than White respondents (adjusted odds ratio 0.50, 95% CI 0.30‐0.83). Overall, 86.7% (n=1408) of participants reported having received a formal IC/BPS diagnosis, and the single strongest determinant of receiving any form of treatment was having a formal diagnosis (odds ratio 29.67, 95% CI 18.32‐48.05). Over 25% (n=385) of all respondents reported using narcotic or opioid medications, indicating the challenging nature of IC/BPS symptom management. ConclusionsMinority or multiple-race participants were significantly less likely to have ever been diagnosed with IC/BPS by a health care professional, and those who were not diagnosed with IC/BPS were less likely to have used self-care behavioral and nonpharmacological treatments for their symptoms. Streamlining the diagnostic process and public health awareness campaigns outlining treatment options may help individuals manage IC/BPS symptoms.